2023
DOI: 10.3390/jof9020252
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dissection of Crz1 and Its Dynamic Subcellular Localization in Cryptococcus neoformans

Abstract: Across lower eukaryotes, the transcription factor Crz1 is dephosphorylated by calcineurin, which facilitates Crz1 translocation to the nucleus to regulate gene expression. In the fungal pathogen Cryptococcus neoformans, calcineurin–Crz1 signaling maintains calcium homeostasis, thermotolerance, cell wall integrity, and morphogenesis. How Crz1 distinguishes different stressors and differentially regulates cellular responses is poorly understood. Through monitoring Crz1 subcellular localization over time, we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Intriguingly, the residue S103 of Crz1, which becomes phosphorylated upon CKA1 deletion, has been previously reported to be critical for Crz1 function ( 43 ). To further explore this, we deleted CKA1 in a strain expressing Crz1-mCherry ( 44 ) and assessed Crz1’s nuclear translocation efficiency (see Fig. S7 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, the residue S103 of Crz1, which becomes phosphorylated upon CKA1 deletion, has been previously reported to be critical for Crz1 function ( 43 ). To further explore this, we deleted CKA1 in a strain expressing Crz1-mCherry ( 44 ) and assessed Crz1’s nuclear translocation efficiency (see Fig. S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…For visualizing the localization of Crz1-mCherry, P CRZ1 -Crz1-mCherry (NEO) (JL334) ( 44 ), and P CRZ1 -Crz1-mCherry (NEO) cka1 Δ (YSB11149) strains were first cultured in YPD at 30°C. They were then diluted with fresh YPD media to an OD 600 of 0.2 and incubated at 23°C until an OD 600 of 0.8 was achieved.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, combined mutation of Crz1 and P-body targets does not recapitulate the phenotypes of calcineurin deletion, suggesting that additional substrates may be important for calcineurin functions [ 24 ]. A recent study revealed that Crz1 also localizes to stress granules and septa upon heat stress, similar to calcineurin [ 26 ]. Interestingly, the study found that Crz1 localizes to stress granules prior to its translocation to the nucleus hinting at the possibility that calcineurin might be dephosphorylating Crz1 at stress granules.…”
Section: What Are Calcineurin’s Substrates?mentioning
confidence: 99%